Structure and Ionic Conductivity of Li2S–P2S5 Glass Electrolytes Simulated with First-Principles Molecular Dynamics - Baba, Takeshi; Kawamura, Yoshiumi (Frontiers in Energy Research, 2016)
Lithium thiophosphate-based materials are attractive as solid electrolytes in all-solid-state lithium batteries because glass or glass-ceramic structures of these materials are associated with very high conductivity. In this work, we modeled lithium thiophosphates with amorphous structures and investigated Li+ mobilities by using molecular dynamics calculations based on density functional theory (DFT-MD). The structures of xLi2S-(100 - x)P2S5 (x = 67, 70, 75, and 80) were created by randomly identifying appropriate compositions of Li+, PS43-, P2S74-, and S2- and then annealing them with DFT-MD calculations. Calculated relative stabilities of the amorphous structures with x = 67, 70, and 75 relative to crystals with the same compositions were 0.04, 0.12, and 0.16 kJ/g, respectively. The implication is that these amorphous structures are metastable. There was good agreement between calculated and experimental structure factors determined from X-ray scattering. The differences between the structure factors of amorphous structures were small, except for the first sharp diffraction peak, which was affected by the environment between Li and S atoms. Li+ diffusion coefficients obtained from DFT-MD calculations at various temperatures for picosecond simulation times were on the order of 10-3 - 10-5 Angstrom2/ps. Ionic conductivities evaluated by the Nernst-Einstein relationship at 298.15 K were on the order of 10-5 S/cm. The ionic conductivity of the amorphous structure with x = 75 was the highest among the amorphous structures because there was a balance between the number density and diffusibility of Li+. The simulations also suggested that isolated S atoms suppress Li+ migration.